Reflexões sobre criatividade na produção escrita de alunos do ensino médio - Souza, Maria Rita Pereira de (2006)
In our practice, we have been verifying that the creativity lack is a constant in the students' compositions, once these reveal enormous difficulties with regard to the writing. Ahead of this verification, we question us I eat we can develop the potential creator of our educandos, since the current teaching is directed to the contents memorization and to don't think it ? We believe don't be possible to point some solution, but we intend prove that some creative considered abilities eat: The humor, the fluency, the fantasy, the originality, the curiosity, the sensibility, the analogy, inconformismo and the elaboration can be stimulated by means of the prático and of the training. With seen to reach such goal, we proposed us to analyze, in students compositions, just the humor abilities, fluency and analogy. Considering that the critical thought is always in connection with the thought creator in the school learning, to the we analyze the creative considered abilities, establish a link with the critical thought. Corpus used to the materialization of this experiment were students' compositions of E. E. Prof.ª Luzia de Queiroz and Oliveira , situated in the Zone East, São Paulo. To base this research, we use I eat theoretical support: The directed authors to the School Psychology and Creativity: Alencar, Freire, Kneller, Ostrower and Wechsler; The directed authors to the Philosophy: Lipman and Raths and the directed authors to Lingüística textual: Koch, Rodari and Matos. With the result of analysis, we certify us that the creative considered texts own characteristic that differ them of the too much texts and prove the creativity lack in the compositions majority, once this ones didn't introduce the creative considered abilities. Worried with this deficiency, we offer in this research some proposed of eat bloom the thought creator of the as bloom the thought creator of the educating